Travelling the Korosko Road Archaeological Exploration in Sudan's Eastern Desert - Davies, W. Vivian; Welsby, Derek A. (Archaeopress Publishing, 2020)
This volume publishes accounts of archaeological exploration carried out during the last 30 years or so in the Sudanese Eastern Desert. It is divided into two related parts.The first and foremost covers results from the work of the Centro Ricerche sul Deserto Orientale (CeRDO), which is based at Varese in northern Italy. Between 1989 and 2006, CeRDO, directed by the brothers Alfredo and Angelo Castiglioni, ran a pioneering programme of expeditions, which traversed the so-called 'Korosko Road' (the main desert route connecting Egypt and Sudan) and followed multiple other tracks throughout the Eastern Desert. They encountered in the process a rich archaeological landscape, hundreds of previously undocumented sites, many frequented over millennia, prominent among them gold-production areas and their associated settlements. The CeRDO record, the photographic database, the material retrieved, to which several of the papers published here are devoted, are now all the more valuable, in that many of these sites have since been badly disturbed and some entirely destroyed by recent goldmining activities.The second part, introduced by a concise account of the historical usage of the Korosko Road, reports in full on a single, short season of documentation, organized in 2013 under the auspices, and with the support, of the Sudan Archaeological Research Society. Its main aim was detailed recording of a group of pharaonic rock-inscriptions discovered by CeRDO expeditions, most located along the Korosko Road and almost all related to the colonial gold-working industry. The project included also a degree of investigation and mapping of the wider context, as well as the recording and study of associated archaeological material, in particular of ceramic remains. The results complement and usefully extend in part those of CeRDO.